Knowledge sharing and sustainable competitive advantage: The role of higher education innovation capability - Santati, Parama; Yuliani, Yuliani; Hadjri, Muhammad Ichsan; Siregar, Lina Dameria; Nasirun, Noraini (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2023)
In this dynamic environment, knowledge sharing and innovation capabilities have become new sources of organizational competitive advantage. As an organization that builds and disseminates knowledge, the role of sharing knowledge in higher education institutions is very important in achieving its goals. In addition, innovation is very important because education plays an important role in creating a sustainable future. This study aims to analyze the role of knowledge sharing in sustainable competitive advantage mediated by the innovation capabilities of tertiary institutions in South Sumatra Province. Data were collected from 207 respondents representing 15 private higher education institutions in South Sumatra Province which were selected purposively. Data analysis used structural equation modeling with the LISREL 8.7 application. The results of the study concluded that knowledge sharing and innovation capabilities had a positive and significant effect on the sustainable competitive advantage of higher education institutions. The research also proves that innovation capabilities partially mediate the relationship between knowledge sharing and sustainable competitive advantage of higher education institutions in South Sumatra Province.